ASSESSMENT OF COMPASSION SATISFACTION AMONG INTENSIVE CARE UNIT NURSES AT TERTIARY CARE HOSPITAL - Ali Zaman, Laraib Latif, Yasir Khan, Sheraz Khan, Sumbul Sheraz, Abdullah Muhammad Zaman, Nazia Shuaib, Amir Sultan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Intensive care unit (ICU) is one of the crucial and specialized area of the hospital that required trained staff with latest and technical instruments and devices, standards and protocols. The aim of the study was to determine the level of compassion satisfaction among nurses working in ICU.Methodology: The study was conducted in the tertiary care hospitals of Khyber pukhtankhwa Pakistan having cross-sectional descriptive design from February to may 2022.The total sample size was 190 using convenient sampling technique, while data was collected through valid and reliable questionnaire. The study was approved by ethical review committee while informed consent was taken from each participants. SPSS 22 was used for data analysis, while ANNOVA for differences and Pearson correlation test was applied for association of CS with demographic data.Results: In the current study majority of the participants were female 131 (68.9%), aged 22 to 25 years 80 (42.1%), and education of 4 years BSN 92 (48.4%). The leading factors that have high mean score of CS  among ICU nurses were:  that I am proud that I can do what is good for patients (4.81 ± 0.51), followed by that I have happy thoughts and feelings that I could help the patients (4.72 ± 0.56), and my works make me feel satisfied (4.63 ± 0.80).Conclusion: The study concluded that maximum number of nurses compassion satisfaction were high in ICU regarding their work. The work environment can benefit from an understanding of the components of professional quality of life